Aspects Of Customary And Cultural Law On The Preservation Of Springs And River Environments - Maria Francisca Mulyadi (President University, 2016)
Customary law is a source of local wisdom inherited from ancestors in the form of culture and customs. In its development, people adapt in the form of custom norms, cultural values, and environmental management activities. Local people who live side by side with nature have knowledge passed down from generation to generation about how to fulfill the necessities of life without destructing nature so traditional local wisdom is very profitable in maintaining the environment and preventing the occurrence of environmental damage. With the advancement of technology and the needs of society has led to the loss of local wisdom that causes barren forests and automatically turns off the springs, in addition to the river environment becomes dirty and not awake.This research is analytical and explorative descriptive, with the aim of obtaining a description of customary law in local wisdom can provide protection the springs and river environment. As a normative study, data is obtained tracing legal documents.By restoring the elements of customary law in community life to grow local wisdom. The principle of local wisdom is to synergize with nature, so that the use of water resources used sufficiently not excessive and provide a ban aimed at preserving the springs. By using enough water then the use of natural resources will be used sufficiently to pay attention to the restrictions aimed at preserving the environment, in this case not clearing forests for plantation land or settlements will make the forest sustainably automatic source of water will be maintained.